Neutral Axis Depth versus Ductility and Plastic Rotation Capacity on Bending in Lightweight-Aggregate Concrete Beams - Bernardo, Luís (2020)
This article presents an experimental study on the evolution of the neutral axis depth at failure in the critical section with the flexural ductility and plastic rotation capacity of reinforced concrete (RC) lightweight-aggregate concrete (LWAC) beams. For this, the results of a previous experimental program involving RC LWAC beams tested in flexure until failure are used. The variable studies were the concrete compressive strength (between 22.0 and 60.4 MPa and dry density between 1651 and 1953 kg/m3) and the longitudinal tensile reinforcement ratio (between 0.13% and 2.69%). The flexural ductility and the plastic rotation capacity of the RC LWAC beams are characterized by a ductility index and a plastic trend parameter, respectively. The influence of the variable studies, as well as the relation of the flexural ductility and plastic rotation capacity with the values for the neutral axis depth at failure are analyzed and discussed. Some conclusions are drawn which can be useful for the design of RC LWAC beams for flexure. In particular, it is shown that the practical rule of limiting the neutral axis depth at failure to ensure ductile behavior, as used in normal-weight aggregate concrete beams, is also valid for RC LWAC beams.